Carbon nanotube molding, electrode for electrochemical water splitting, method for producing the same, and electrochemical water splitting device
A carbon nanotube molded body with enhanced specific surface area, mechanical strength, and pore distribution, supported with optimized platinum, addresses the limitations of existing electrodes for electrochemical water splitting, achieving efficient hydrogen production with reduced platinum usage.
Patent Information
- Application Number
- JP2023092151
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-05
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-06-05
AI Technical Summary
Existing carbon nanotube molded bodies used as carriers for electrochemical water splitting electrodes lack sufficient specific surface area, mechanical strength, and pore distribution, limiting their effectiveness in hydrogen production.
A carbon nanotube molded body with a specific surface area of 700 m²/g or more, pore distribution of 3 to 15 nm, tensile strength of 45 MPa or more, and Young's modulus of 1600 MPa or more, optimized for use in electrochemical water splitting electrodes, supported with platinum in the range of 11 to 154 μg/cm², and manufactured through a method involving dispersion, drying, washing, and carbonization without monosaccharides.
The carbon nanotube molded body enhances the electrochemical water splitting performance by maintaining high catalytic activity and mechanical stability, reducing platinum usage, and improving electron transfer efficiency, resulting in superior hydrogen production capabilities.
Smart Images

Figure 2024174360000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a carbon nanotube molded body, an electrode for electrochemical water splitting and a method for producing the same, and an electrochemical water splitting device. [Background technology]
[0002] Water electrolysis (electrochemical water splitting) is considered a promising method for producing hydrogen. Platinum-based catalysts are most effective for electrochemical water splitting in hydrogen production. However, platinum reserves on Earth are insufficient, so advanced methods are needed to reduce the amount of platinum supported while maintaining high efficiency. Because the activity of a catalyst depends on the active sites on the catalyst surface, the support material plays an important role in electrode fabrication.
[0003] In recent years, carbon nanotubes have attracted attention due to their excellent properties such as high electrical conductivity, excellent thermal conductivity, and large specific surface area, and it has been proposed to mold carbon nanotubes into various shapes and use them in various products. For example, JP 2022-121865 A (Patent Document 1) describes a carbon nanotube molded body containing carbon nanotubes, in which the density of the carbon nanotube molded body is 0.55 g / cm 3 or more, and the specific surface area of the carbon nanotube molded body is 500 m 2 In order to use a carbon nanotube sheet obtained by forming the carbon nanotube into a sheet as a support for the above-mentioned electrodes, the carbon nanotube sheet needs to have even better physical properties than before, such as a specific surface area and mechanical strength. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2022-121865 Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made to solve the above-mentioned problems, and its object is to provide a novel carbon nanotube molded body that has sufficient physical properties such as specific surface area and mechanical strength even when used as a support for an electrode for electrochemical water splitting, an electrode for electrochemical water splitting using the same, a method for manufacturing the same, and an electrochemical water splitting device. [Means for solving the problem]
[0006] The present invention relates to a carbon nanotube molded body containing carbon nanotubes, 2 / g or more, the pore distribution of the carbon nanotube molded body is 3 to 15 nm, the tensile strength of the carbon nanotube molded body is 45 MPa or more, and the Young's modulus of the carbon nanotube molded body is 1600 MPa or more.
[0007] In the carbon nanotube molded article of the present invention, the carbon content in the carbon nanotube molded article is preferably 98 mass % or more.
[0008] The carbon nanotube molded article of the present invention is preferably a carbon nanotube sheet.
[0009] The present invention also relates to a method for producing a ferroelectric material having a specific surface area of 700 m 2 The present invention also provides an electrode for electrochemical water splitting, comprising a carbon nanotube molded body having a molecular weight of 1.0 μm / g or more, a pore distribution of 3 to 15 nm, a tensile strength of 45 MPa or more, and a Young's modulus of 1600 MPa or more, and platinum supported on the carbon nanotube molded body.
[0010] In the electrode for electrochemical water splitting of the present invention, the amount of platinum supported is 11 to 154 μg / cm 2 It is preferable that the range is within the range of 100 μm.
[0011] In the electrode for electrochemical water splitting of the present invention, it is preferable that the carbon nanotube molded body is a carbon nanotube sheet, and that the carbon nanotube sheet is supported on the surface of a metal structure, or on the surface of a carbon fiber or a carbon fiber structure made of carbon fiber.
[0012] The present invention also relates to a method for producing a polymer having a specific surface area of 700 m 2 The present invention also provides an electrochemical water splitting device comprising a carbon nanotube molded body having a molecular weight of 1.0 / g or more, a pore distribution of 3 to 15 nm, a tensile strength of 45 MPa or more, and a Young's modulus of 1600 MPa or more, and an electrochemical water splitting electrode including platinum supported on the carbon nanotube molded body.
[0013] In the electrochemical water splitting device of the present invention, the amount of platinum supported on the electrodes for electrochemical water splitting is 11 to 154 μg / cm 2 It is preferable that the range is within the range of 100 μm.
[0014] In the electrochemical water splitting device of the present invention, it is preferable that the carbon nanotube molding in the electrode for electrochemical water splitting is a carbon nanotube sheet, and that the carbon nanotube sheet is supported on the surface of a metal structure, or on the surface of carbon fiber or a carbon fiber structure made of carbon fiber.
[0015] The present invention further provides a method for producing a carbon nanotube molded product containing carbon nanotubes, the method comprising the steps of: mixing a dispersion liquid containing carbon nanotubes, a dispersant, and a dispersion medium, and not containing monosaccharides, with a solution containing cellulose nanofibers and not containing monosaccharides to obtain a mixture not containing monosaccharides; supplying the obtained mixture to a mold and drying it to obtain a solidified product containing carbon nanotubes; washing the solidified product and removing the dispersant from the solidified product; calcining the solidified product to carbonize the cellulose nanofibers; and performing an activation treatment on the surface of the solidified product after calcination.
[0016] The present invention also provides a method for producing an electrode for electrochemical water splitting, comprising a step of depositing platinum by magnetron sputtering onto the carbon nanotube molded body obtained by the method for producing a carbon nanotube molded body of the present invention. Effect of the Invention
[0017] According to the present invention, it is possible to provide a novel carbon nanotube molded body that has sufficient physical properties such as specific surface area and mechanical strength even when used as a support for an electrode for electrochemical water splitting, an electrode for electrochemical water splitting using the same, a method for manufacturing the same, and an electrochemical water splitting device. [Brief description of the drawings]
[0018] [Figure 1] 1 is a graph showing the results of measuring the specific surface area by a BET method for carbon nanotube sheet samples 1 to 4 in Experimental Example 1. [Diagram 2] 1 is a graph showing the results of measuring pore distribution for Samples 1 to 4 of the carbon nanotube sheet in Experimental Example 1. [Diagram 3] 1 is a graph showing the results of strength evaluation of samples 3 and 4 of carbon nanotube sheets in Experimental Example 1 described later. [Figure 4] 1 is a graph showing the results of component analysis by an XPS method for carbon nanotube sheet sample 4 in Experimental Example 1. [Diagram 5] 1 is a graph showing the results of measuring the sp2 / sp3 ratio by Raman spectroscopy for Samples 1 to 6 in Experimental Example 1. [Figure 6] 1 is a photograph showing an electrode for electrochemical water splitting of the present invention actually obtained in Experimental Example 1. [Figure 7] 1 is a photograph showing platinum supported on a single carbon nanotube in an actually obtained electrode for electrochemical water splitting of the present invention. [Figure 8]The results observed by atomic resolution TEM are shown in Figure 8(a) for carbon (C), Figure 8(b) for oxygen (O), and Figure 8(c) for platinum (Pt). [Figure 9] 9A and 9B show high-resolution spectra of the electrodes for electrochemical water splitting of the present invention, where FIG. 9(a) is the spectrum of C1s before electrochemical water splitting, FIG. 9(b) is the spectrum of C1s after electrochemical water splitting, FIG. 9(c) is the spectrum of Pt4f before electrochemical water splitting, and FIG. 9(d) is the spectrum of Pt4f after electrochemical water splitting. [Figure 10] 1 is a graph showing the results of an electrocatalytic activity evaluation (three-electrode cell) in Experimental Example 1, using current density / overpotential as an index. [Figure 11] 1 is a graph showing the evaluation results of cycle characteristics (platinum loading: 11.5 g / cm 2 ) in Experimental Example 1. [Figure 12] 1 is a graph showing the evaluation results of catalyst turnover number (TOF: Turn Over Frequency) in Experimental Example 1. [Figure 13] 1 is a graph showing a Tafel Plot in Experimental Example 1. [Figure 14] 1 is a graph showing the evaluation results of hydrogen reduction current density per unit mass of a platinum catalyst (Pt mass specific activity) corresponding to each overpotential in Experimental Example 1. [Figure 15] Photographs showing high-magnification images of SWCNT sheets at each stage. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] [Carbon nanotube compact] The carbon nanotube molded body of the present invention has excellent specific surface area, pore distribution, tensile strength and Young's modulus, all of which are superior to conventional carbon nanotube molded bodies, and is particularly suitable for use as a support for electrodes for electrochemical water splitting.
[0020] FIG. 1 is a graph showing the results of measuring the specific surface area by the BET method for carbon nanotube sheet samples 1 to 4 in Experimental Example 1 described later (sample 4 that has been subjected to an activation treatment corresponds to the "electrode for electrochemical water splitting" of the present invention described later, and the carbon nanotube sheet of sample 4 corresponds to the "carbon nanotube molded body" of the present invention). The vertical axis shows the adsorption capacity (cm 3 / g STP, the horizontal axis is relative pressure (p / p 0 The carbon nanotube molded article of the present invention has a length of 700 mm. 2 / g or more, preferably 800m 2 / g or more, more preferably 1000m 2 The carbon nanotube molded article of the present invention has a specific surface area of 700 m 2 When the specific surface area of the carbon nanotube molded article of the present invention is less than 700 m / g, a large number of large bundles (aggregates of carbon nanotubes) are contained, which causes a problem of inhibiting the support of atomic cluster-class catalysts. 2 / g or more, the higher the specific surface area, the better, but in order to increase the specific surface area, the carbon nanotubes must be oxidized, and the oxidation process may cause damage to the carbon nanotubes. In order to maintain the excellent electronic conductivity of the carbon nanotubes, the specific surface area of the carbon nanotube molded product of the present invention is set to 1500 m 2 / g or less, and 2 It is more preferable that the molecular weight is not more than 1 / g.
[0021] FIG. 2 is a graph showing the results of measuring the pore distribution of samples 1 to 4 of the carbon nanotube sheet carrying platinum in Experimental Example 1 described later, and the vertical axis is dv / dlog(D) (cm 3 The horizontal axis represents the pore size (nm) and the horizontal axis represents the pore size (nm). The carbon nanotube molded product of the present invention has a pore size distribution in the range of 3 to 15 nm. The carbon nanotube sheet "Sample 1" after the deionized water washing / alcohol washing treatment contains a dispersant, stabilizer, residual catalyst, etc., so the pore size distribution is about 3 nm and the porosity is also 0.05 cm 3 / g or less. The carbon nanotube sheet "Sample 2" after the nitric acid treatment is not a suitable structure for supporting an atomic cluster-class catalyst. When the pore distribution of the carbon nanotube molded body is less than 3 nm, the total number of pores is small, so the carbon nanotube sheet exhibits the properties of a flat sheet, and there are problems such as no pores or low porosity, low or no water penetration, and a high amount of polymer surfactant, which results in relatively low electrical conductivity. On the other hand, when the pore distribution of the carbon nanotube molded body exceeds 15 nm, there is a problem such as low active surface area. In addition, from the viewpoint of improving water penetration and active surface area, the cell distribution of the carbon nanotube molded body of the present invention is preferably within the range of 7 to 15 nm, and more preferably within the range of 9 to 14 nm.
[0022] FIG. 3 is a graph showing the results of strength evaluation of samples 3 and 4 of the carbon nanotube sheet in Experimental Example 1 described later at 23° C., and sample 4 at −60° C. and 300° C. by the JIS method, with the vertical axis being tensile stress (MPa) and the horizontal axis being tensile strain (%). The carbon nanotube molded body of the present invention has a tensile strength of 45 MPa or more, preferably 50 MPa or more, and more preferably 60 MPa or more. If the tensile strength of the carbon nanotube molded body is less than 45 MPa, it is prone to breakage due to bending, making it difficult to handle. The tensile strength of the carbon nanotube molded body of the present invention is preferably as high as 45 MPa or more, but the carbonization treatment and oxidation treatment must be reduced, and in that case, the polymer surfactant remains, causing a decrease in surface area and electrical conductivity. For this reason, the tensile strength of the carbon nanotube molded body of the present invention is preferably 70 MPa or less, more preferably 65 MPa or less. The carbon nanotube molded body of the present invention also has a Young's modulus of 1600 MPa or more, preferably 1800 MPa or more, and more preferably 2000 MPa or more. If the Young's modulus of the carbon nanotube molded product is less than 1600 MPa, it has poor elasticity and is damaged and deformed when pulled. The higher the Young's modulus of the carbon nanotube molded product of the present invention is, the better, as long as it is 1600 MPa or more, but the carbonization and oxidation treatments must be reduced, and in that case, the polymer surfactant remains, reducing the surface area and electrical conductivity. Therefore, the Young's modulus of the carbon nanotube molded product of the present invention is preferably 2400 MPa or less, and more preferably 2000 MPa or less.
[0023] It is preferable that the carbon nanotube molded body of the present invention does not crack when subjected to a bending test in which the body is bent 1 million times. This allows for excellent flexibility. Generally, metal molded bodies break after about 100,000 times bending. The bending test can be performed using a bending tester (DeMacha bending tester (manufactured by Yasuda Seiki Seisakusho Co., Ltd.)) in an environment with a temperature of 23°C to 27°C and a relative humidity of 30% to 70%.
[0024] Fig. 4 is a graph showing the results of component analysis by XPS for Sample 4 of the carbon nanotube sheet in Experimental Example 1 described later, where Fig. 4(a) shows the results of scanning over a wide range, and Fig. 4(b) shows the results of scanning over a narrow range, with the vertical axis showing C / S and the horizontal axis showing bond energy (eV). Fig. 5 is a graph showing the results of measuring the sp2 / sp3 ratio by Raman spectroscopy for Samples 1 to 6 in Experimental Example 1 described later, with the vertical axis showing intensity (number) and the horizontal axis showing Raman shift (cm -1 ). The carbon content in the carbon nanotube molded body of the present invention is preferably 98% by mass or more, more preferably 98.5% by mass or more, and particularly preferably 99.0% by mass or more. If the carbon content in the carbon nanotube molded body is less than 98% by mass, the carbon nanotube molded body contains metal impurities, which tend to adversely affect the performance of the catalyst and the addition of platinum on the carbon nanotubes. The carbon content in the carbon nanotube molded body of the present invention is preferably as high as 98% by mass or more, but the carbon nanotube molded body must be treated with a strong acid, which damages the carbon nanotube molded body, and the price of the carbon nanotube molded body increases depending on the purity. For these reasons, the carbon content in the carbon nanotube molded body is preferably 99.5% by mass or less, and more preferably 99.0% by mass or less.
[0025] The shape of the carbon nanotube molded product of the present invention is not particularly limited, and may be, for example, a sheet shape, an arch shape, a ring band shape, a belt shape, a thread shape, etc. Among these, the carbon nanotube molded product is preferably a carbon nanotube sheet because it can be suitably used for an electrode for electrochemical water splitting, which will be described later.
[0026] [Electrode for electrochemical water splitting] The present invention is a method for producing a 700m2 2 The present invention also provides an electrode for electrochemical water splitting, comprising a carbon nanotube molded body having a surface area of 100 nm / g or more, a pore distribution of 3 to 15 nm, a tensile strength of 45 MPa or more, and a Young's modulus of 1600 MPa or more, and platinum (Pt) supported on the carbon nanotube molded body. Here, Fig. 6 is a photograph showing the electrode for electrochemical water splitting of the present invention actually obtained in Experimental Example 1 described later. Fig. 7 is a photograph (10,000,000 times) showing platinum supported on one carbon nanotube in the actually obtained electrode for electrochemical water splitting of the present invention, and Fig. 8 shows the results of observation with an atomic resolution TEM, with Fig. 8(a) showing the results for carbon (C), Fig. 8(b) showing the results for oxygen (O), and Fig. 8(c) showing the results for platinum (Pt).
[0027] FIG. 9 shows high-resolution spectra of the electrode for electrochemical water splitting of the present invention measured using a PHI500 VersaProbe (ULVAC-PHI). FIG. 9(a) shows the spectrum of C1s before electrochemical water splitting, FIG. 9(b) shows the spectrum of C1s after electrochemical water splitting, FIG. 9(c) shows the spectrum of Pt4f before electrochemical water splitting, and FIG. 9(d) shows the spectrum of Pt4f after electrochemical water splitting. FIG. 9(c) shows prominent peaks at 71.4 eV and 74.8 eV corresponding to Pt4f7 / 2 and 4f5 / 2, respectively. When this peak was deconvoluted, three chemical isotope peaks corresponding to Pt(0), Pt(II), and Pt(IV), respectively, were observed at 71.2 eV, 72.4 eV, and 73.7 eV. Figures 9(a) and (b) also show that the C1s spectrum shows that after platinum loading, the peaks corresponding to sp2 hybridization decrease and sp3 hybridization increases. Detailed analysis proves that metallic platinum is dominant and there is a strong interaction between the metal and the substrate. Thus, in the electrochemical water splitting electrode of the present invention, sub-nano-sized platinum atomic clusters consisting of tens to hundreds of Pt atoms are supported on a carbon nanotube molded body. This allows the active surface (111 surface) of the platinum catalyst to be fully utilized, and the HOMO-LOMO interaction between the platinum atomic cluster and the carbon nanotube molded body can be utilized to achieve an ultra-long life of the platinum catalyst. Supporting platinum nanoparticles on a carbon-based composite material is a promising method for improving catalytic activity for electrochemical water splitting, and by precisely controlling the carbon material, a desirable nanostructure with a high specific surface area and abundant active sites can be obtained. The strong interaction and synergistic effect between the metal species and the carbon support can effectively prevent the accumulation and elution of metal nanoparticles during the electrochemical process. Furthermore, the improved electrical conductivity of the substrate allows for high-speed electron transfer, resulting in excellent catalytic activity. Here, the size, shape, and position of the platinum nanoparticles on the carbon nanotube play an important role in catalytic activity, since the catalytic activity depends on the quality of the substrate and the platinum nanoparticles. However, in most composite materials, only the surface atoms are involved in electrochemical water splitting, so nanoparticles limit the availability of platinum atoms to the particle core, making them ineffective. Reducing the size of platinum nanoparticles would significantly reduce the amount of precious metal used and increase catalytic activity, which would have the effect of lowering the cost of electrocatalysts.
[0028] In the electrode for electrochemical water splitting of the present invention, the amount of platinum supported is 11 to 154 μg / cm 2 When using platinum at the atomic level, it is necessary to optimize the amount of platinum on the carbon nanotube. The nanoparticles must be as small as possible, uniformly aligned, and not excessive. Therefore, the range is 11 to 117 μg / cm. 2 It is more preferable that the platinum loading is within the range of 11 μg / cm 2 When the platinum loading is less than 154 μg / cm, the amount of platinum is too low to generate a sufficient current, and a high voltage tends to be required. 2If the amount of platinum exceeds 100%, the amount of platinum on the independent carbon nanotubes becomes excessive, and if the amount of platinum becomes excessive, aggregation occurs during the electrochemical reaction, which tends to reduce performance. The electrode for electrochemical water splitting of the present invention can make maximum use of the active surface (111 surface) of the platinum catalyst, and therefore can exhibit significantly superior electrochemical water splitting ability with a much smaller amount of platinum supported than in the past.
[0029] FIG. 10 is a graph showing the results of an electrode catalyst activity evaluation (three-electrode cell) using current density / overpotential as an index in Experimental Example 1 described later, with the vertical axis representing current density J (mA / cm 2 ), and the horizontal axis is overpotential (V vs RHE). From the results shown in Figure 10, 2 , and the platinum loading is also the same (117±5μg / cm 2 ), the overpotential of the electrochemical water splitting electrode of the present invention is 23 mV, the overpotential of the commercially available electrochemical water splitting electrode is 115 mV, and the amount of platinum catalyst supported is 11 ± 5 μg / cm 2 That is, even when the catalyst loading amount was reduced to 1 / 10 of that of the commercially available product, it was confirmed that the overpotential of the electrode for electrochemical water splitting of the present invention was 42 mV, that is, smaller than the overpotential of the commercially available electrode for electrochemical water splitting.
[0030] FIG. 11 shows the cycle characteristics (platinum loading: 11.5 μg / cm) in Experimental Example 1 described later. 2 ) is a graph showing the evaluation results, and the vertical axis is the current density J (mA / cm 2 11, the horizontal axis is overpotential (V vs. RHE), and it can be seen from Fig. 11 that the electrode for electrochemical water splitting of the present invention exhibited sufficient recyclability even after 300 cycles.
[0031] FIG. 12 is a graph showing the evaluation results of the catalyst turnover number (TOF: Turn Over Frequency) in Experimental Example 1 described later, and the vertical axis is TOF (s -1The horizontal axis is the overpotential (V vs RHE) and the horizontal axis is the overpotential (V vs RHE). From Figure 12, the catalyst turnover number (TOF), which is an index showing how many moles of substrate molecules are converted to products per mole before the catalyst becomes inactive in a catalytic reaction, shows that the platinum loading of 30 μg / cm 2 Even in the following, it is clear that the electrode for electrochemical water splitting of the present invention has excellent TOF characteristics.
[0032] FIG. 13 is a graph showing a Tafel Plot in Experimental Example 1 described later, in which the vertical axis represents overpotential (mV) and the horizontal axis represents log j (mAcm -2 ) The Tafel slope was calculated from the Tafel equation, i.e., an experimental plot showing the relationship between the electrochemical reaction rate and overpotential. Based on this Tafel slope, it was found that the catalyst develops in three steps: the Volmer step, the Heyrovsky step, and the Tafel step.
[0033] FIG. 14 is a graph showing the evaluation results of the hydrogen reduction current density per unit mass of the platinum catalyst (Pt mass specific activity) corresponding to each overpotential in Experimental Example 1 described later, where the vertical axis is the mass specific activity (A / mgcm 2 14, the horizontal axis is overpotential (V vs RHE). From Fig. 14, the hydrogen reduction current density per unit mass of the platinum catalyst corresponding to each overpotential, i.e., the Pt mass specific activity, also suggests that the catalytic activity of the electrochemical water splitting electrode of the present invention with a Pt loading of 30 µg or less exceeds that of the commercially available product for comparison, and thus the performance is superior as a whole characteristic.
[0034] In the electrode for electrochemical water splitting of the present invention, the carbon nanotube molded body is preferably a carbon nanotube sheet, and the carbon nanotube sheet is supported on the surface of a metal structure, or on the surface of carbon fibers or a carbon fiber structure made of carbon fibers. By providing such a configuration, it is possible to increase the electrical conductivity, increase the mechanical strength, and have long-term stability, thereby improving the overall effect of electrochemical water splitting.
[0035] The metal constituting the metal structure is preferably titanium, platinum, gold, nickel, molybdenum, silver, cobalt, or iron, and particularly preferably titanium, because it increases the current density, reduces the loss of free electrons, and enhances the HER effect. When the carbon nanotube sheet is supported on the surface of a metal structure, there is an advantage that the internal resistance of the water electrolysis cell is lower and the mechanical strength is higher than when the carbon nanotube sheet is supported on the surface of carbon fiber or a carbon fiber structure made of carbon fiber.
[0036] When the carbon nanotube sheet is supported on the surface of carbon fibers or a carbon fiber structure made of carbon fibers, the carbon nanotube sheet is stable for a long period of time in an acidic environment and the weight of the water electrolysis cell is lighter than when the carbon nanotube sheet is supported on the surface of a metal structure. In addition, the carbon fibers or the carbon fiber structure made of carbon fibers are porous and have a high porosity, which has the advantage of allowing high water and gas permeability.
[0037] When applied to an electrode for electrochemical water splitting of the present invention, the shape of the carbon nanotube molded article of the present invention is preferably a sheet shape (i.e., a carbon nanotube sheet) as described above, but is not limited to this. For example, taking advantage of its excellent flexibility and durability, it may be formed into an arch shape, a ring band shape, a belt shape, a thread shape, or the like.
[0038] The electrode for electrochemical water splitting of the present invention supports platinum as a catalyst for electrochemical water splitting, but other conventional catalysts for electrochemical water splitting such as iridium oxide may also be used instead of platinum.
[0039] The electrode for electrochemical water splitting of the present invention can be particularly suitably applied to the electrochemical water splitting device of the present invention described below, but can also be applied, without particular restriction, to various conventionally known applications using electrodes using platinum as a catalyst, such as electrolytic water conditioners, hydrogen water production devices, portable hydrogen water production devices, strongly acidic water generation devices, drinking water supply devices, ionized beverage drinking devices, liquid activation / electrolysis devices, electrolytic water production evaluation devices, various batteries (secondary batteries, lead-acid batteries, dye-sensitized solar cells, fuel cells, biofuel cells, etc.), and various sensors (water quality sensors, hydrogen sensors, gas sensors, biosensors, alcohol sensors, condensation sensors, etc.).
[0040] [Electrochemical water splitting device] The present invention also relates to a method for producing a polymer having a specific surface area of 700 m 2 The present invention also provides an electrochemical water splitting device comprising an electrochemical water splitting electrode including a carbon nanotube molded body having a molecular weight of 1000 g / g or more, a pore distribution of 3 to 15 nm, a tensile strength of 45 MPa or more, and a Young's modulus of 1600 MPa or more, and platinum supported on the carbon nanotube molded body. The electrochemical water splitting device of the present invention is provided with the electrochemical water splitting electrode of the present invention described above, and can exhibit electrochemical water decomposition ability that is significantly superior to conventional devices. The electrochemical water splitting device of the present invention is not particularly limited in other configurations as long as it is provided with the electrochemical water splitting electrode of the present invention described above, and other configurations may be used in appropriate combination with those used in conventional electrochemical water splitting devices.
[0041] In the electrochemical water splitting device of the present invention, the amount of platinum supported on the electrodes for electrochemical water splitting is 11 to 154 μg / cm 2 It is preferable that the range is within the range of 100 μm.
[0042] Also in the electrochemical water splitting device of the present invention, it is preferable that the carbon nanotube molding in the electrode for electrochemical water splitting is a carbon nanotube sheet, and that the carbon nanotube sheet is supported on the surface of a metal structure, or on the surface of carbon fiber or a carbon fiber structure made of carbon fiber.
[0043] [Method of manufacturing carbon nanotube molded body] The present invention also provides a method for producing a carbon nanotube molded body, which can suitably produce a carbon nanotube molded body having the above-mentioned excellent specific surface area, pore distribution, tensile strength, and Young's modulus. The method for producing a carbon nanotube molded body of the present invention includes the steps of: mixing a dispersion containing carbon nanotubes, a dispersant, and a dispersion medium and not containing monosaccharides with a solution containing cellulose nanofibers and not containing monosaccharides to obtain a mixture not containing monosaccharides; feeding the obtained mixture into a mold and drying it to obtain a solidified product containing carbon nanotubes; washing the solidified product and removing the dispersant from the solidified product; calcining the solidified product to carbonize the cellulose nanofibers; and performing an activation treatment on the surface of the solidified product after calcination.
[0044] In the method for producing a carbon nanotube molded body of the present invention, first, a dispersion containing carbon nanotubes, a dispersant and a dispersion medium but not containing monosaccharides is mixed with a solution containing cellulose nanofibers but not containing monosaccharides to obtain a mixture not containing monosaccharides.
[0045] The carbon nanotubes used in the present invention may be either single-walled or multi-walled, but it is preferable to use single-walled carbon nanotubes (SWCNTs) because they have excellent electrical and thermal conductivity.
[0046] The diameter of the carbon nanotube is preferably within the range of 0.5 to 2 nm, and more preferably within the range of 1 to 1.5 nm, because a small diameter is recommended due to physical, electrical and structural properties. The diameter of the carbon nanotube can be measured using a transmission electron microscope (TEM), and the diameter of 10 carbon nanotubes is measured and the arithmetic average value is defined as the diameter of the carbon nanotube.
[0047] The length of the carbon nanotube is preferably within the range of 0.5 to 3 μm, more preferably within the range of 1 to 2 μm, since a long carbon nanotube with a small diameter exhibits a high aspect ratio and thus improves the properties of the carbon nanotube, and furthermore, the network structure is maintained, and if the length is too long, it is difficult to obtain a high dispersion effect. The length of the carbon nanotube can be measured using an atomic force microscope (AFM), and the arithmetic average value of the lengths of 10 carbon nanotubes is taken as the length of the carbon nanotube.
[0048] Examples of the dispersion medium include water, a water-soluble organic solvent, or a mixture thereof. Among these, water is preferred from the viewpoint of reducing environmental load. Examples of water include distilled water, ion-exchanged water, and ultrapure water. Examples of the water-soluble organic solvent include alcohols (methanol, ethanol, isopropanol, isobutanol, sec-butanol, tert-butanol, methyl cellosolve, ethyl cellosolve, ethylene glycol, glycerin, etc.), ethers (ethylene glycol dimethyl ether, 1,4-dioxane, tetrahydrofuran, etc.), ketones (acetone, methyl ethyl ketone), N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.
[0049] The dispersant is for dispersing carbon nanotubes. Examples of dispersants include ionic surfactants such as cationic surfactants, anionic surfactants, and amphoteric surfactants, nonionic surfactants, disaccharides such as sucrose, maltose, lactose, cellobiose, and trehalose, oligosaccharides such as cyclodextrin, steroid derivatives such as bile acid, cholesterol, and cholic acid, DNA, π-conjugated polymers, and phthalocyanine derivatives. Among these, steroid derivatives, especially bile acid, are preferred for the following reasons. Carbon nanotubes are hydrophobic, so when a steroid derivative is added as a dispersant, the hydrophobic group of the steroid derivative is bound to the surface of the carbon nanotube, and the carbon nanotube is pulled, making it easy for the carbon nanotube to be isolated and dispersed.
[0050] The content of the dispersant needs to be optimized to reduce the amount of dispersant used without affecting the electrical conductivity of the carbon nanotubes (increasing the amount of dispersant improves dispersion efficiency but decreases electrical conductivity), so it is preferable that the content of the dispersant is within the range of 2 to 5 mass % relative to the content of the carbon nanotubes, and more preferably within the range of 3 to 4 mass %.
[0051] The diameter of the cellulose nanofiber is preferably within the range of 0.7 to 4 nm, and more preferably within the range of 1 to 2 nm, for reasons of functionality and maintaining mechanical and chemical properties. The diameter of the cellulose nanofiber can be measured using an atomic force microscope (AFM), and the diameter of 10 cellulose nanofibers is measured and the arithmetic average value is taken as the diameter of the cellulose nanofiber.
[0052] The length of the cellulose nanofibers is required to a certain extent to maintain the dispersion effect in the solvent, but on the other hand, if the length is too short, the property of protecting the carbon nanotubes cannot be maintained, so the length is preferably within the range of 1 to 5 μm, and more preferably within the range of 2 to 3 μm. The length of the cellulose nanofibers can be measured using an atomic force microscope (AFM), and the arithmetic average value of the lengths of 10 cellulose nanofibers is taken as the length of the cellulose nanofibers.
[0053] The ratio of length to diameter of the cellulose nanofiber (length / diameter, aspect ratio) is preferably within the range of 1,000 to 5,000 for mechanical and structural properties, as well as for maintaining the optimal dispersion effect of the carbon nanotubes and cellulose nanofibers and their network structure.
[0054] Solvents that can be used for the solution containing cellulose nanofibers and no monosaccharides include, for example, dimethyl sulfoxide, n-methyl-2-pyrrolidone, water, etc., and among these, water is preferred because it is easy to obtain a uniform dispersion effect, is low-cost, and is eco-friendly.
[0055] Neither the dispersion containing carbon nanotubes nor the solution containing cellulose nanofibers contains monosaccharides. Examples of monosaccharides include arabinose, ribose, xylose, glucose, mannose, galactose, fructose, sorbose, rhamnose, fucose, ribosaccharides, etc. By mixing these dispersions and solutions, a mixture containing no monosaccharides is obtained.
[0056] The ratio of the mass of cellulose nanofiber to the mass of carbon nanotubes in the mixture needs to be optimized to reduce the amount of cellulose nanofiber used without affecting the electrical conductivity of the carbon nanotubes (increasing the amount of cellulose nanofiber improves the quality of the carbon nanotube network but reduces electrical conductivity). Also, because the amount of amorphous carbon increases after carbonization, the ratio is preferably in the range of 0.05 to 1, and more preferably in the range of 0.2 to 0.5.
[0057] Next, the mixture is fed into a mold and dried to obtain a solidified material containing carbon nanotubes. The mold may be appropriately selected depending on the shape of the carbon nanotube molded product to be produced. For example, when producing a carbon nanotube sheet, a tray can be used as the mold. Drying is performed in a temperature environment of, for example, 25 to 80°C.
[0058] Next, the solidified material is washed to remove the dispersant from the solidified material. Specifically, the solidified material is first washed with a polar organic solvent such as alcohol. This makes it possible to remove the dispersant used in dispersing the carbon nanotubes. Next, the solidified material is washed with an acid. This makes it possible to remove impurities (such as catalysts) derived from the process in the manufacture of the carbon nanotubes. It is preferable to adjust the concentration of the acid to within a range of 45 to 60 mass %. Examples of the acid include hydrochloric acid and nitric acid. Finally, the solidified material is washed with deionized water until it becomes neutral. After washing the solidified material, it is preferable to dry the solidified material. The drying here is also performed in a temperature environment of, for example, 25 to 80°C.
[0059] Next, the solidified product is calcined to carbonize the cellulose nanofibers. Calcination is carried out, for example, in a nitrogen atmosphere at a temperature in the range of 600 to 800°C. In this process, the cellulose nanofibers are carbonized to become amorphous carbon particles, which are then removed from the carbon nanotube solidified product by washing with subcritical water, thereby obtaining a high-purity carbon nanotube molding. The calcination time can be, for example, 60 to 120 minutes.
[0060] Finally, the surface of the fired solidified product is subjected to an activation treatment. For example, the activation treatment is performed by heating the carbon nanotube molded body to a temperature in the range of 800 to 900°C in a carbon dioxide atmosphere to activate the carbon nanotube molded body. The heating time for the activation treatment can be, for example, 30 to 60 minutes.
[0061] [Method of manufacturing electrodes for electrochemical water splitting] The present invention further provides a method for producing an electrode for electrochemical water splitting, comprising a step of depositing platinum on a carbon nanotube molded body obtained by the above-mentioned method for producing a carbon nanotube molded body of the present invention by magnetron sputtering. Magnetron sputtering can be suitably performed using, for example, an LL-type High-density General Purpose Sputtering System (CFS-4EP-LL, manufactured by i-Miller). Depositing platinum on a carbon nanotube molded body by magnetron sputtering has the advantages of maintaining uniformity and accurately controlling the film thickness, obtaining a platinum deposition area with a diameter of 15 cm or more, and being inexpensive, as compared with other methods (for example, atomic layer deposition (ALD), metalorganic chemical vapor deposition (MOCVD), and physical vapor deposition (PVD)).
[0062] As described above, when the carbon nanotube molded body in the electrode for electrochemical water splitting of the present invention is a carbon nanotube sheet, and the carbon nanotube sheet is supported on the surface of a metal structure, or on the surface of carbon fibers or a carbon fiber structure made of carbon fibers, the carbon nanotube sheet can be supported by spraying the Nafion dispersion onto the surface of the metal structure, placing the carbon nanotube sheet, and drying it, in the case of the surface of a metal structure, spraying the Nafion dispersion onto the surface of the metal structure, placing the carbon nanotube sheet, and drying it, in the case of carbon fibers, spraying the Nafion dispersion onto the surface of the metal structure, placing the carbon nanotube sheet, and drying it, or by spraying the Nafion dispersion onto the surface of the carbon fiber structure, placing the carbon nanotube sheet, and drying it, or by sandwiching both sides of the carbon nanotube sheet with carbon fibers and applying hot press.
[0063] The present invention will be described in more detail below with reference to experimental examples, but the present invention is not limited to these.
[0064] <Experimental Example 1> Ultra-long TUBALL purchased from OCSiAl Ltd as carbon nanotubes (商標) SWCNTs were used. Reagent grade 0.5M sulfuric acid and 60% nitric acid were purchased from Fujifilm Wako Pure Chemical Industries, Ltd. TEMPO-CNF (2.0 wt%) manufactured by the Isogai method and purchased from Nippon Paper Industries Co., Ltd. was used as cellulose nanofibers.
[0065] 7.5 g of TUBALL SWCNT powder, 15 g of sodium cholate (dispersant), and 10 g of polyvinylpyrrolidone (stabilizer) were pre-dispersed in 1000 mL of deionized water for 12 h using a ball mill (Masuda Universal Ball Mill Model UBM 2). The mixture was then processed in a bead mill (Multi Lab DYNO Mill) containing 0.6 mm zirconium beads until a good dispersion was obtained.
[0066] The SWCNT dispersion was mixed with an appropriate amount of cellulose nanofiber solution (solvent: water) in various ratios. The resulting mixture was then poured into a tetrafluoroethylene tray and dried at room temperature (25 °C). The dried sheet was soaked in 80% ethanol and peeled off. The surfactant was removed from the sheet by repeated washing with ethanol and digestion with concentrated nitric acid. The SWCNT sheet was then carbonized under nitrogen atmosphere and then activated under carbon dioxide gas at 900 °C in a tube furnace.
[0067] The activated SWCNT sheet was cut into 1 cm × 1 cm pieces and placed in the chamber of a magnetron sputtering system (LL-type High-density General Purpose Sputtering System (CFS-4EP-LL, manufactured by i-Miller). After pretreatment, a platinum metal film was formed using an argon beam.
[0068] (Materials Characterization) The morphology and element distribution of the samples were observed using JEOL scanning electron microscopes (JSM6390, JSM-7500FA, and JSM-7000F). Transmission electron microscopy (TEM) analysis was performed using a high-contrast electron microscope (JEM-1400, manufactured by JEOL). X-ray photoelectron spectroscopy (XPS) was performed using a multifunctional scanning XPS PHI5000 VersaProbe (ULVAC-PHI) manufactured by Beckman Coulter SA (商標) Brunauer, Emmett, and Teller (BET) specific surface areas were determined from nitrogen adsorption-desorption isotherms using a 3100 analyzer. Pyrolysis tests were performed using an SII EXSTAR 6000 TG / DTA analyzer. Raman spectra were measured using a Renishaw inVia Raman microscope equipped with a 532 nm laser and calibrated against a silicon wafer as a reference. Nuclear Reaction Analysis (NRA) measurements were performed at the Microanalysis Laboratory, Tandem Accelerator (MALT), University of Tokyo.
[0069] Further, the strength was evaluated as follows. Test Company:DJK Test method: Compliant with JIS K 7127 (JIS K 7161-1) Measurement items: Tensile strength, tensile (nominal) strain, tensile modulus Specimen shape: Specimen type 2, strip 10 x 200 (mm) Test pieces were cut out, and because the samples were brittle, the gripping areas were reinforced with tape and the samples were sandwiched between rubber sheets before testing.
[0070] The evaluation is based on the following sample: Sample 1: SWCNT sheet after washing with ethanol Sample 2: SWCNT sheet after washing with nitric acid Sample 3: SWCNT sheet after carbonization Sample 4: Activated SWCNT sheet (corresponding to the "electrochemical water splitting electrode" of the present invention) Sample 5: SWCNT sheet before cleaning Sample 6: CNT 75% The measurements were performed on the following samples. Fig. 1 is a graph showing the results of measuring the specific surface area by the BET method for samples 1 to 4, Fig. 2 is a graph showing the results of measuring the pore distribution for samples 1 to 4, Fig. 3 is a graph showing the results of strength evaluation for samples 3 and 4, Fig. 4 is a graph showing the results of component analysis by the XPS method for sample 4, and Fig. 5 is a graph showing the results of measuring the sp2 / sp3 ratio by Raman spectroscopy for samples 1 to 6. The measured values for samples 1 to 4 are shown in Table 1.
[0071] [Table 1]
[0072] 7 is a photograph (10,000,000x) of platinum supported on one carbon nanotube of sample 4, taken with an atomic resolution elemental mapping structural analysis microscope (JEM-ARM200F Thermal FE STEM, manufactured by JEOL Ltd.). Sample 4 was also observed with an atomic resolution elemental mapping structural analysis microscope (JEM-ARM200F Thermal FE STEM, manufactured by JEOL Ltd.), and the results are shown in FIG. 8(a) for carbon (C) (10,000,000x), FIG. 8(b) for oxygen (O) (10,000,000x), and FIG. 8(c) for platinum (Pt) (10,000,000x).
[0073] In addition, using a PHI500 VersaProbe (ULVAC-PHI), the C1s spectrum before electrochemical water splitting for sample 4 is shown in Figure 9(a), the C1s spectrum after electrochemical water splitting is shown in Figure 9(b), the Pt4f spectrum before electrochemical water splitting is shown in Figure 9(c), and the Pt4f spectrum after electrochemical water splitting is shown in Figure 9(d). In Figure 9(c), there are prominent peaks at 71.4 eV and 74.8 eV corresponding to Pt4f7 / 2 and 4f5 / 2, respectively. When this peak was deconvoluted, three types of chemical isotope peaks corresponding to Pt0, PtII, and PtIV were observed at 71.2 eV, 72.4 eV, and 73.7 eV, respectively. In addition, Figures 9(a) and (b) show that the peaks corresponding to sp2 hybridization decreased and sp3 hybridization increased in the C1s spectrum after platinum loading. Detailed analysis demonstrated that metallic platinum dominates and that there is a strong interaction between the metal and the substrate.
[0074] (Electrochemical properties) A glassy carbon electrode (GCE, diameter 3 mm) obtained from CHI Instruments was used to measure the platinum loading of 11 μg / cm 2 , 28μg / cm 2 , 57μg / cm 2 , 117μg / cm 2 , 125μg / cm 2 , 154μg / cm 2Electrochemical analysis was performed by loading SWCNT sheets of the activated Pt / C on the GCE. The GCE was polished using polished diamonds suspended in distilled water on a diamond polishing pad and alumina powder suspended in distilled water on an alumina polishing pad. After the first and second polishing steps, the electrodes were thoroughly washed with deionized water. Before loading the catalyst, the GCE electrodes were washed again by immersing them in an isopropanol solution and sonicating for about 10 seconds. 2 μl of 0.5 wt% Nafion in ethanol was dropped onto the washed GCE. The platinum-deposited SWCNT sheets were carefully cut into circles with a diameter of 3 mm and placed on the GCE before drying the Nafion. The electrodes were dried overnight at ambient conditions for further use. Typically, 50 mg of commercial Pt / C (Pt loading: 5%) powder was dispersed in 1 mL of Nafion solution (0.5 wt% in ethanol) and sonicated in an ultrasonic bath for 30 min to prepare a homogeneous ink. 4 μl of this Pt-containing ink was deposited on a GCE to prepare a Pt / C electrode. Electrocatalytic activity testing was performed in a standard three-electrode system using an electrochemical analyzer model CHI 760E, CH Instruments. 0.5 M H2SO4, platinum coil, and Ag / AgCl electrodes were used as the electrolyte solution (deionized water containing 0.5 M sulfuric acid), counter electrode, and reference electrode. The scan rate was 10 mV / sec. Figure 10 shows the results of such electrocatalytic activity evaluation (three-electrode cell) using current density / overpotential as an index, with the vertical axis showing current density J (mA / cm 2 ), and the horizontal axis is overpotential (V vs RHE). From the results shown in Figure 10, 2 , and the platinum loading is also the same (117±5μg / cm 2 ), the overpotential of the electrochemical water splitting electrode of the present invention is 23 mV, the overpotential of the commercially available electrochemical water splitting electrode is 115 mV, and the amount of platinum catalyst supported is 11 ± 5 μg / cm 2 That is, even when the catalyst loading amount was reduced to 1 / 10 of that of the commercially available product, it was confirmed that the overpotential of the electrode for electrochemical water splitting of the present invention was 42 mV, that is, smaller than the overpotential of the commercially available electrode for electrochemical water splitting.
[0075] The electrocatalytic activity test was carried out in a standard three-electrode system using an electrochemical analyzer model CHI 760E, CH Instruments. 0.5M H2SO4, platinum coil, and Ag / AgCl electrodes were used as the electrolyte solution (deionized water containing 0.5M sulfuric acid), counter electrode, and reference electrode. The scan speed was 10mV / s. The scan range was a potential range of 0V to -0.26V, and the number of cycles was 3000. The cycle characteristics (platinum loading: 11.5μg / cm2) were evaluated using the current density / overpotential as an index for the electrocatalytic activity evaluation (three-electrode cell). 2 The graph in FIG. 11 shows the results of the evaluation of the current density J (mA / cm 2 11, the horizontal axis is overpotential (V vs. RHE), and it can be seen from Fig. 11 that the electrode for electrochemical water splitting of the present invention exhibited sufficient recyclability even after 3000 cycles.
[0076] The amount of platinum metal was quantitatively measured using inductively coupled plasma atomic emission spectrometry (ICP-AES). The catalytic turnover number (TOF) for electrochemical water splitting was calculated using the following formula:
[0077]
number
[0078] Platinum loading is 11μg / cm 2 , 28μg / cm 2 , 57μg / cm 2 , 117μg / cm 2 , 125μg / cm 2 , 154μg / cm 2 Figure 12 shows the results of evaluating the catalyst turnover number (TOF: Turn Over Frequency) for the SWCNT sheet after activation treatment. The vertical axis is TOF (s-1 / Pt-site) and the horizontal axis is overpotential (V vs RHE). Figure 12 shows that the catalyst turnover number (TOF), an index showing how many moles of substrate molecules are converted to products per mole before the catalyst becomes inactive in a catalytic reaction, is sufficient for a platinum loading of 30 μg / cm. 2Even in the following, it is clear that the electrode for electrochemical water splitting of the present invention has excellent TOF characteristics.
[0079] The electrocatalytic activity test was performed in a standard three-electrode system using an electrochemical analyzer model CHI 760E, CH Instruments. 0.5M H2SO4, platinum coil, and Ag / AgCl electrodes were used as the electrolyte solution (deionized water containing 0.5M sulfuric acid), counter electrode, and reference electrode. The scan rate was 10mV / sec. Figure 13 shows the results of the electrocatalytic activity evaluation (three-electrode cell) using the current density / overpotential as an index. The vertical axis shows the overpotential (V vs RHE) and the horizontal axis shows the current density J (mA / cm 2 ) is the common logarithm of the Tafel equation, i.e., the Tafel slope was calculated from an experimental plot showing the relationship between the rate of electrochemical reaction and overpotential. Based on this Tafel slope, it was found that the catalyst develops in three steps as shown in the following equation.
[0080]
number
[0081] The electrocatalytic activity test was performed in a standard three-electrode system using an electrochemical analyzer model CHI 760E, CH Instruments. 0.5M H2SO4, platinum coil, and Ag / AgCl electrodes were used as the electrolyte solution (deionized water containing 0.5M sulfuric acid), counter electrode, and reference electrode. The scan rate was 10mV / sec. Figure 14 shows the results of the evaluation of the hydrogen reduction current density per unit mass of the platinum catalyst (Pt mass specific activity) corresponding to each overpotential. The vertical axis shows the mass specific activity (A / mgcm 2 14, the horizontal axis is overpotential (V vs RHE). From Fig. 14, the hydrogen reduction current density per unit mass of the platinum catalyst corresponding to each overpotential, i.e., the Pt mass specific activity, also suggests that the catalytic activity of the electrochemical water splitting electrode of the present invention with a Pt loading of 30 µg or less exceeds that of the commercially available product for comparison, and thus the performance is superior as a whole characteristic.
[0082] (Consideration) To utilize carbon nanotubes for various applications, a tubular dispersion is an important step. Dispersants and stabilizers are essential elements for making high-quality SWCNT dispersions. Also, for the carbon nanotube sheet to stand on its own, it is necessary to effectively remove the polymer components. The polymers used in Experimental Example 1 (e.g., sodium cholate, polyvinylpyrrolidone) are highly soluble in ethanol. Therefore, the carbon nanotube sheet was first washed several times with ethanol and then decomposed with concentrated nitric acid. However, cellulose nanofibers are not soluble in either ethanol or nitric acid. Therefore, it was found that the carbon nanotube network was supported by the support of cellulose nanofibers. The remaining cellulose nanofibers were removed by washing with water and carbonization.
[0083] Detailed structural observation of the SWCNT sheet at each stage was performed using a scanning electron microscope (SEM), and the high-magnification images are shown in Figure 15. The photographs in Figure 15 are of the following stages (A to D are 40 μm thick).
[0084] A: Before cleaning (20,000x) B: After cleaning (20,000x) C: When cellulose nanofiber was not used (50,000x) D…Cellulose nanofibers used to support platinum (50,000x) E…Thickness 10nm, low magnification (100,000x) F…Thickness 10nm, high magnification (150,000x) G…Thickness 20nm, low magnification (75000x) H…Thickness 20nm, high magnification (150,000x) In Figure 15, A shows that the unwashed SWCNT sheet does not have a porous structure, and all the pores are filled with surfactant and polymer. However, when the dispersant and polymer are removed, the pore structure becomes visible, as in Figure 15, B. As the carbon nanotube strands become longer, the tendency for each carbon nanotube to bend increases. In Experimental Example 1, ultra-long single-walled carbon nanotubes (TUBALL) with an average length of 1 to 2 μm were fabricated. (商標) Since we used SWCNTs, a strong filler is required to straighten the carbon nanotubes. Cellulose nanofibers are a strong filler during sheet casting and help straighten the ultra-long SWCNTs. The importance of cellulose nanofibers can be easily illustrated by comparing C and D in Figure 15. In C in Figure 15, the individual carbon nanotubes were curved due to the absence of cellulose nanofibers, but as shown in D in Figure 15, the presence of cellulose nanofibers straightened the individual carbon nanotubes. D in Figure 15 confirmed that a continuous interconnected porous structure with nano-sized pores was obtained. The carbon nanotubes were tightly connected, and a continuous interconnected network was developed inside the SWCNT sheet as visible (D in Figure 15).
[0085] Figure 15E-H are high-resolution SEM images of the platinum-loaded SWCNT sheets, clearly showing that platinum is remarkably uniform and smoothly coated on the individual SWCNT sheet fibers. The platinum was not randomly deposited on the SWCNT sheet, but was selectively coated on the individual carbon nanotube strands. A high-magnification image of a 10 nm thick platinum-coated sample (Figure 15F) shows that the pores are very clean and no clusters are found. A high-magnification image of a 20 nm thick platinum-loaded SWCNT sheet (Figure 15H) shows that the porosity decreases with increasing platinum layer thickness, which may block the electrolyte.
[0086] Figure 1 shows the nitrogen adsorption and desorption isotherms of samples 1 to 4, which were found to follow a type IV isotherm. A type IV isotherm has a hysteresis loop associated with capillary condensation in mesopores, and the P / P 0 At higher isotherms, adsorption becomes limited. The initial part of the isotherm is due to monolayer-multilayer adsorption on the mesopore walls, which is the same pathway as the corresponding part of the type II isotherm, but is followed by pore condensation. More specifically, the fit of the isotherms in Figure 1 to the type IV(a) isotherm shows that in larger mesopores (>4 nm), capillary condensation leads to hysteresis.
[0087] The BET specific surface area of the carbon nanotube sheet after ethanol washing is 59m 2 / g, which is very small compared to the original 75% SWCNT powder. When treated with nitric acid, the specific surface area gradually increased (305 m 2 The surface area of the carbon nanotube sheet after carbonization is 545 m 2 / g, with an average pore size of about 9.8 nm. At this stage, all the unremoved polymers and cellulose nanofibers have turned into small amorphous clusters, giving the carbon nanotube sheet a mesoporous structure. Carbon reacts with carbon dioxide during activation to form carbon monoxide (gasification) and produce microspores. Therefore, optimal activation of the carbonized carbon nanotube sheet resulted in a pore size of 1031 m. 2 A significant BET surface area of 1.0 µm / g is obtained. The carbon dioxide also helps to remove the amorphous carbon clusters trapped within the carbon nanotube network and opens up all the available pores, increasing the average pore size to 13.5 nm.
[0088] In the Raman spectrum (Figure 5), the 1590 cm vibration, which is due to the in-plane vibration of a six-membered ring, which is familiar in carbon-based materials, is observed. -1 A G-band peak was confirmed near the G-band peak. In carbon nanotubes, the G-band is decomposed and split into G+ and G-. G+ (1593 cm -1 ) corresponds to the longitudinal mode in the carbon nanotube axial direction, and G-(1572 cm -1) corresponds to a transverse wave mode perpendicular to the axis. 1339cm -1 The band observed around 350 to 100 cm is called the D band and is related to defects and disorders in carbon nanotubes such as amorphous carbon, vacancies, and heteroatoms. -1 In the region of , SWCNTs give rise to a series of bands corresponding to radial breathing modes (RBM) where they expand and contract in the radial direction (not shown). The intensity ratio of the G band to the D band (G / D ratio) is used to evaluate the defects of carbon nanotubes. The calculated G / D ratio of powdered SWCNTs was 51, and that of the carbon nanotube sheet after activation treatment was 49. This result proves that optimal activation does not increase the defects of carbon nanotubes. Since amorphous carbon is less stable than carbon nanotubes, its reactivity with carbon dioxide during activation was higher than that of carbon nanotubes. However, it was found that the higher the gas flow rate, the higher the reactivity of carbon nanotubes with carbon dioxide, resulting in a gradual increase in defects.
[0089] The SWCNT sheet prepared in Experimental Example 1 is flexible and foldable, and has promising mechanical strength. Typical stress-strain curves of SWCNT sheet samples at various temperatures are shown in Figure 3. Young's modulus and tensile strength can be extracted from the stress-strain curves. From the data, it is confirmed that both carbonized and activated SWCNT sheets (samples 3 and 4) exhibit high tensile properties. Tensile strength is highly dependent on thickness, and the recommended thickness of the SWCNT sheet is 50-60 μm. In addition, the SWCNT sheet can withstand temperatures of 300°C and -60°C.
[0090] The elemental composition and chemical state of the samples were evaluated by XPS analysis (Figure 4). The C1s deconvoluted peaks are at 284.4 and 285.6 eV, respectively, corresponding to sp2 (C-C bonds) and sp3 (C-O) hybridization. The O1s deconvoluted peaks are at 530.9, 531.5, and 532.3 eV, corresponding to physisorbed O, OH, and C-OH. The purity of the CNTs can be determined by the percentage of sp2 hybridized carbon atoms, which increases with the washing treatment. In conjunction with the Raman spectra, the XPS results demonstrate that sp2 bonds are dominant in the SWCNT sheets.
[0091] The high-resolution Pt4f spectrum of the platinum-loaded SWCNT sheet (Figure 9) has prominent peaks at 71.4 eV and 74.8 eV corresponding to Pt 4f7 / 2 and 4f5 / 2, respectively. When this peak was deconvoluted, three chemical isotope peaks were observed at 71.2 eV, 72.4 eV, and 73.7 eV corresponding to Pt(0), Pt(II), and Pt(IV), respectively (Figure 9(c) and (d)). The C1s spectrum of the SWCNT showed that after platinum coating, the peaks corresponding to sp2 hybridization decreased and sp3 hybridization increased. Detailed analysis demonstrated that metallic platinum was dominant, proving the strong interaction between the metal and the substrate (Figure 9(a) and (b)).
[0092] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims.
Claims
1. A carbon nanotube molding containing carbon nanotubes, The specific surface area of the carbon nanotube molded body is 700 m 2 / g or more, The carbon nanotube molding has a pore distribution of 3 to 15 nm; The carbon nanotube molding has a tensile strength of 45 MPa or more; The carbon nanotube molded body has a Young's modulus of 1600 MPa or more.
2. 2. The carbon nanotube molded body according to claim 1, wherein the carbon content in the carbon nanotube molded body is 98 mass % or more.
3. The carbon nanotube molded body according to claim 1 , wherein the carbon nanotube molded body is a carbon nanotube sheet.
4. Specific surface area is 700m 2 / g or more, a pore distribution of 3 to 15 nm, a tensile strength of 45 MPa or more, and a Young's modulus of 1600 MPa or more; and platinum supported on the carbon nanotube molded body.
5. Platinum loading is 11 to 154 μg / cm 2 5. The electrode for electrochemical water splitting according to claim 4, wherein the surface area of the electrode is in the range of
6. the carbon nanotube molding is a carbon nanotube sheet, 5. The electrode for electrochemical water splitting according to claim 4, wherein the carbon nanotube sheet is supported on a surface of a metal structure, or on a surface of carbon fiber or a carbon fiber structure made of carbon fiber.
7. Specific surface area is 700m 2The electrochemical water splitting device comprises a carbon nanotube molded body having a molecular weight of 1.0 / g or more, a pore distribution of 3 to 15 nm, a tensile strength of 45 MPa or more, and a Young's modulus of 1600 MPa or more, and an electrochemical water splitting electrode including platinum supported on the carbon nanotube molded body.
8. The amount of platinum supported in the electrode for electrochemical water splitting is 11 to 154 μg / cm 2 The electrochemical water splitting apparatus of claim 7 , wherein the temperature is within the range of
9. the carbon nanotube molded body in the electrode for electrochemical water splitting is a carbon nanotube sheet, 8. The electrochemical water splitting device according to claim 7, wherein the carbon nanotube sheet is supported on a surface of a metal structure, or on a surface of carbon fiber or a carbon fiber structure made of carbon fiber.
10. A method for producing a carbon nanotube molded body containing carbon nanotubes, comprising the steps of: A step of mixing a dispersion liquid containing carbon nanotubes, a dispersant and a dispersion medium, but not containing monosaccharides, with a solution containing cellulose nanofibers, but not containing monosaccharides, to obtain a mixture not containing monosaccharides; supplying the mixture to a mold and drying to obtain a solidified material containing carbon nanotubes; washing the solidified material to remove the dispersant from the solidified material; A step of calcining the solidified material to carbonize the cellulose nanofibers; A process of performing an activation treatment on the surface of the solidified material after firing; The method for producing a carbon nanotube molded article includes the steps of:
11. 11. A method for producing an electrode for electrochemical water splitting, comprising the step of depositing platinum by magnetron sputtering on the carbon nanotube molded body obtained by the method according to claim 10.
Citation Information
Patent Citations
Electric energy generating system
JP2002056852A
Carbon nanotube aggregate and carbon nanotube film
JP2018145027A
Fuel cell
JP2019075277A
Nanocellulose-nanocarbon composite structure and production method of the same
JP2020164378A
Method for producing carbon nanotube molded body and carbon nanotube molded body
JP2022121865A
Cited By
Carbon nanotube aggregates, conductive materials, electrodes, secondary batteries, planar aggregates, laminates, filters, electromagnetic shielding, and pellicles for extreme ultraviolet radiation.
JP2026129628A
Carbon nanotube aggregates, conductive materials, electrodes, secondary batteries, planar aggregates, laminates, filters, electromagnetic shielding, and pellicles for extreme ultraviolet radiation.
JP2026164684A
Carbon nanotube aggregates, conductive materials, electrodes, secondary batteries, planar aggregates, laminates, filters, electromagnetic shielding, pellicles for extreme ultraviolet radiation, and methods for measuring mean curvature.
JP2026164686A
Carbon nanotube aggregates, conductive materials, electrodes, secondary batteries, planar aggregates, laminates, filters, electromagnetic wave shields, and pellicles for extreme ultraviolet rays
JP7785233B1
Carbon nanotube aggregates, conductive materials, electrodes, secondary batteries, planar aggregates, laminates, filters, electromagnetic wave shields, and pellicles for extreme ultraviolet rays
JP7785234B1
